Pengaruh Strategi Pembelajaran Think Talk Write dalam Kelompok Kecil Terhadap Kemampuan Berpikir Kreatif dan Pemahaman Pada Siswa MTs Negeri 2 Medan - Muhammad Arif Hidayat (Intiqad: Jurnal Agama dan Pendidikan Islam, 2019)
This study uses a combined technique between quantitative and qualitative research to see a variable that is the Think Talk Write learning strategy on students' creative understanding and thinking as a variable that accompanies the learning strategy variable Think Talk Write. The sample in this study were students of class VII1 and VII2 at MTsN 2 Medan in Langkat District with 40 students in the experimental class and 40 students in the control class. The conclusions of this study are as follows; 1) Class VII students of MTsN 2 Medan who obtained the Think Talk Write learning strategy approach showed that the understanding of the History of Islamic Culture was significantly better compared to students who had regular learning; 2) Creative thinking of class VII students of MTsN 2 Medan who obtained learning with the learning strategy approach of Think Talk Write showed that it was significantly better compared to students who learned normally; 3) There is a positive correlation between understanding the history of Islamic culture and the ability of students to think creatively. In the experimental group class the results showed that the correlation of understanding of Islamic Culture History to students' creative thinking skills was greater compared to the control group class; 4) The attitude of students to Islamic Culture History lessons, through the learning strategy approach Think Talk Write and on the matter of understanding History Islamic culture and the ability to think creatively are positive; 5) The activities of students who get the Think Talk Write learning strategy approach are more active in learning, especially discussing with friends, and also students are more daring to express or ask questions to the teacher, and be more creative in solving the problems given.